Synthesis of 3-methyl-3,7-dihydro-1н-purine-2,6-dione derivatives and investigations of their physicochemical properties - Aleksandrova, K. V.; Vasylyev, D. A.; Priimenko, B. A.; Александрова, Катерина Вячеславівна; Васильєв, Денис Андрійович; Прийменко, Борис Олександрович (Львівська медична спільнота, 2017)
The reaction of alkylation of 3-methyl-8-mercaptoxanthine was studied. Obtained derivatives of purin-2,6-dione were confirmed using methods of IR-, NMR-spectroscopy and mass-spectrometry. Conducted investigations unambiguously confirm the structure of the synthesized compounds. Нами було вивчено реакції алкілування 3-метил-8-меркаптоксантину. Будову отриманих похідних пурин-2,6- діону було підтверджено методами ІЧ-, ПМР-спектрометрії та мас-спектрометрії. Проведені дослідження повністю підтверджують структуру синтезованих сполук. Нами была изучена реакция алкилирования 3-метил-8-меркаптоксантина. Строение полученных производных пурин-2,6-диона было подтверждено методами ИК-, ПМР-спектрометрии и масс-спектрометрии. Проведенные ис¬следования полностью подтверждают структуру синтезированных соединений.
Keywords: synthesis; purine-2,6-dione; physicochemical properties; spectroscopy; spectrometry; синтез; пурин-2,6-діон; фізико-хімічні властивості; спектроскопія; спектрометрія; пурин-2,6-дион; физико-химические свойства; спектроскопия; спектрометрия